Ira Oscar Glick: At the crossroads of the sociologies of financial markets - Tom Duterme (Finance and Society, 2022)
This review essay looks at the plurality of research conducted today in the sociology of financial markets by examining a pioneering and little-known study - the PhD thesis of Ira Oscar Glick. It is indeed possible to find in this 1957 thesis some insights that are later solidified by several contemporary lines of research in the sociology of financial markets (new economic sociology, science and technology studies, gender studies, Bourdieusian sociology, ethnomethodology, the economics of conventions). This rediscovery of a key author in the history of the field may lead us to reconsider his legacy and delve into a landmark work that potentially still harbors unexplored insights capable of opening up new avenues for research.
Keywords: 300; Sociology of finance; science and technology studies; gender studies; ethnomethodology